Acquiring of a Paradigmatic Prosthetic Abutment by Means of Laboratory Parallelometer - T. Sojka (Czech Dental Chamber, 2009)
3D scanner KaVo PREPassistant is used in dentist's education and research.The aim of presented study was to create a prototypal prosthodontic aboutment for comparison with students' preparations. A laboratory parallelometer was used for preparation and a methylmetacrylic pattern was created to fix the artificial tooth to this device. The result is a pillar with an slope of 6° and with a rounded stair.